Increasing the productivity of rajma through proper sowing date and plant geometry - Pokhrel, Anil; Dangi, Sangharsh Raj (Journal of Agriculture and Natural Resources, 2022)
Rajma (Phaseolus vulgaris L.) cultivation is gaining popularity in Terai to Hills of Nepal. The poor plant establishment and yield due to the results of unsuitable sowing time and row spacing are the main reasons for lower productivity of it. Therefore, the date of sowing and row spacing trials were conducted in two consecutive years, 2017 and 2018 at the Grain Legumes Research Program, Khajura, Banke. A widespread and registered variety of rajma PDR 14 was used in the experiment. The experiment was laid out in a split-plot design with four sowing dates (a) 11th October, (b) 26th October, (c) 10th November and (d) 25th November as the main-factor, and three rows spacing (a) 30 cm, (b) 40 cm and (c) 50 cm as the sub-factor, consisted of three replications. The effect of the date of sowing on all the yield and yield attributing characters was found significant at a one percent significance level. Similarly, row spacing has resulted in a significant difference in grain yield. Rajma sown on 26th October (Kartik 9) produced 12, 38 and 64% higher grain yield than sown on 11th October, 10th November and 25th November, respectively. Moreover, rajma seeds sown on 26th October with 30 cm × 10 cm plant geometry produced the highest grain yield (2185 kg/ha). The narrow row spacing seemed well than the wider row in rajma production. There is a great potential to increase the production and productivity of rajma through an appropriate time of sowing and row spacing.